"+1 for Imgur": A content analysis of SIDE theory and common voice effects on a hierarchical bidirectionally-voted commenting system. (December 2017) - Hale, Brent J.
Abstract: This research is among the first to attempt quantitative analysis of a site-bound digital subculture by identifying commenting regularities, using Imgur as a case study. A theoretical framework using SIDE theory and common voice informs a content analysis of 105 Imgur posts and 4404 comments in which the Imgur subculture is identified. Building on initial qualitative work, quantitative evidence is found for common voice, elucidating the Imgur subculture through identification of strategic commenting strategies. Findings indicate that post content affects commenting strategies, as the prevalence of common voice features varied according to post categorization. Additionally, post categories elicited different levels of common voice, with the community identification and humor categories eliciting the greatest concentration of common voice responses and information/mobilization and social support eliciting the least. Findings also suggest a preference for comments that approve of post content, as approving comments received a higher score and more responses than disapproving comments, while disapproving comments received more reprimanding responses. Results provide evidence that empirical study of site-bound digital subgroups is possible, informing future digital media research by providing a theoretical and methodological framework for examining digital subcultures. Highlights: Documents a site-bound digital subculture by identifying commenting regularities. The common voice concept is quantitatively evidenced through content analysis. Post category found to affect the prevalence of common voice use in comments. Approving comments receive a higher score and more responses than those disapproving. Breaking social norms results in conservative punishment by the community.